Cytokinins induce the development of Campomanesia pubescens root cuttings - Gomes, Francielly Rodrigues; Barbosa, Moab Acácio; Ragagnin, Angelita Lorrayne Soares Lima; Souza, Ana Laura Pereira; Rodrigues, Cláudia Dayane Marques; Silva, Danielle Fabíola Pereira (Comunicata Scientiae, 2021)
The gabirobeira (Campomanesia pubescens) is a species native to Brazilian Cerrado with great potential but is threatened to extinction and remains wild. The nursery plant production is an alternative to solve those problems and the use of plant growth regulators can support vegetative propagation. The objective of this work was to evaluate the effect of cytokinin concentrations on the vegetative propagation of C. pubescens root cuttings. The concentrations of the cytokinin 6-Benzylaminopurine were: 0.0 (Control), 1.0; 2.0 and 4.0 mg L-1 diluted in NaOH solution (6 mol L-1). The cuttings with standard size of 5 cm were dipped in the concentrations for 15 seconds and transplanted in bags containing the substrate Bioplant. After 140 days the number of shoots, length of the shoots, number of leaves, length of the leaves, the diameter of the main stem, the diameter of the main root, the total number of roots, length of the main root, total fresh matter and total dry matter, were evaluated. The experiment was conducted in a completely randomized design, with fifteen replicates per treatment. The data were submitted to analysis of variance and the effects of the concentrations tested and adjusted by regression equations. The lower concentrations of cytokinin were beneficial to the development of the cuttings, while higher concentrations inhibited their development.